2016
DOI: 10.2215/cjn.12261115
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasminuria with Overhydration in Patients with CKD

Abstract: Background and objectives Hypervolemia is a common feature of patients with CKD and associated with hypertension. Recent work has shown stimulation of sodium retention by urinary plasmin during nephrotic syndrome. However, it is unclear whether plasminuria plays a role in patients with stable CKD and non-nephrotic proteinuria.Design, setting, participants, & measurements In this cross-sectional study, we analyzed the fluid status of 171 patients with CKD consecutively presenting to our outpatient clinic from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 31 publications
9
65
1
1
Order By: Relevance
“…We agree with Prof. Ehmke that in nephrotic mice with genetic uPA deletion the formation of plasmin from plasminogen may not be completely suppressed. We also agree that very low concentrations of plasmin are sufficient to cause proteolytic ENaC activation as we have previously shown in vitro . Therefore, we cannot rule out the possibility that in nephrotic uPA knockout mice very low concentrations of urinary plasmin may contribute to proteolytic ENaC activation.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…We agree with Prof. Ehmke that in nephrotic mice with genetic uPA deletion the formation of plasmin from plasminogen may not be completely suppressed. We also agree that very low concentrations of plasmin are sufficient to cause proteolytic ENaC activation as we have previously shown in vitro . Therefore, we cannot rule out the possibility that in nephrotic uPA knockout mice very low concentrations of urinary plasmin may contribute to proteolytic ENaC activation.…”
supporting
confidence: 77%
“…We also agree that very low concentrations of plasmin are sufficient to cause proteolytic ENaC activation as we have previously shown in vitro. 5 Therefore, we cannot rule out the possibility that in nephrotic uPA knockout mice very low concentrations of urinary plasmin may contribute to proteolytic ENaC activation. Importantly, this does not challenge our main conclusion that uPA is not essential for sodium retention in nephrotic syndrome.…”
Section: Dear Editormentioning
confidence: 99%
“…3134 Of interest, a recent study analyzed whether this mechanism could also play a role in patients with CKD who did not have nephrotic-range proteinuria. 35 To this end, the authors performed a cross-sectional study in 171 outpatients with CKD (different cause and stages and varying degrees of proteinuria) and 2 control groups including healthy volunteers and patients with nephrotic syndrome. The investigators found that proteinuria was the strongest independent predictor for hypervolemia, as assessed by bioimpedance spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria is associated with urinary serine protease activity primarily due to aberrant filtration of these proteases across a damaged glomerular filtration barrier (Schork et al. ; Svenningsen et al. , ).…”
Section: Introductionmentioning
confidence: 99%
“…ENaC has a key role in regulation of the extracellular fluid volume and blood pressure, but besides activation by regulatory hormones, specific proteases can activate the channel (Kleyman et al 2009;Orce et al 1980;Passero et al 2008;Vallet et al 1997). Proteinuria is associated with urinary serine protease activity primarily due to aberrant filtration of these proteases across a damaged glomerular filtration barrier (Schork et al 2016;Svenningsen et al 2009Svenningsen et al , 2012. Volume retention in NS was prevented by a protease inhibitor (Bohnert et al 2017).…”
Section: Introductionmentioning
confidence: 99%